(untitled)
" The well-posedness of the Cauchy problem for the system i2202_tu + 220200b2_xu = uv + |u|00b2u, t, x 2208 mathbbR, 2202_tv + 2202_x03972202_xv = 2202_x|u|00b2, u(0, x) = u_0(x), v(0, x) = v_0(x), is considered. It is proved that there exists a unique local solution (u(x, t), v(x, t)) 2208 C([0, T);H^s) 00d70002C([0, T);H^s- frac12 ) for any initial data (u_0, v_0) 2208 H^s( mathbbR) 00d70002H^s- frac12 ( mathbbR)(s 2265 frac14) and the solution depends continuously on the initial data.", number=2, journal=Journal of Partial Differential Equations, year=2004, month=May, pages=137–151